Finding the pathognomonic clinical features, do we still need supporting examinations?: two case reports - Fetriani, Ulfa; Permatasanti, Ayu; Wahyuni, Indah Suasani (Universitas Padjadjaran, 2025)
Introduction: Pathognomonic symptoms often allow for the extablishment of a clinical diagnosis without laboratory-supporting examinations. This article discusses two cases of oral mucosal disease presenting with typical symptoms and pathognomonic clinical features. Through anamnesis, history taking, and physical examination led to the clinical diagnosis of primary herpetic gingivostomatitis and pseudomembranous oral candidiasis. Case report: The first case involved a 30-year-old woman with primary herpetic gingivostomatitis, characterized by multiple ulcers in the oral cavity and lips. The second case was that of a 4-year-old girl with pseudomembranous oral candidiasis, characterized by wipeable whitish plaques on the oral mucosa, which left an erythematous area. Antiviral therapy was given to the herpetic gingivostomatitis patient, while the patient wih pseudomembranous candidiasis received antifungal treatment. Significant clinical improvement was observed within 1-2 weeks following adequate treatment. Supporting examinations were not performed due to the pathognomonic clinical features. Conclusion: Primary herpetic gingivostomatitis and acute pseudomembranous candidiasis exhibit pathognomonic clinical features that are typical and generally sufficient for clinical diagnosis without laboratory-supporting confirmation. If clinical diagnosis-based treatment results in improvement, supporting examination may not be necessary. Therefore, strict supervision from a doctor is mandatory in this situation.